2022
DOI: 10.1002/nau.24879
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin for treating overactive bladder in men: A systematic review

Abstract: Purpose We sought to systematically review the literature on the use of botulinum toxin (BTX‐A) injections in the bladder to treat overactive bladder (OAB) in men. Materials and methods A systematic review was performed to identify clinical trials on efficacy and safety of BTX‐A injections in the detrusor for treatment of OAB in men published from inception to October 2020. Quality assessment was performed using the Cochrane Collaboration's tool for assessing risk of bias and study characteristics were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The pharmacotherapy of OAB relies essentially on the use of two β 3 -adrenergic agonists: vibegron ( Gemtesa ® , FDA-approved in 2020) and mirabegron ( Myrbetriq ® , FDA-approved in 2012) with a comparable limited efficacy, even if vibegron, with less side effect on blood pressure, is often preferred to mirabegron [ 5 , 6 , 7 , 8 ]. A few other options are available, including the use of botulinum toxin A, neuromodulation with implantable devices, and laser treatment but their efficacy is limited [ 9 , 10 , 11 ]. The search for novel treatment modalities and drugs continues.…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacotherapy of OAB relies essentially on the use of two β 3 -adrenergic agonists: vibegron ( Gemtesa ® , FDA-approved in 2020) and mirabegron ( Myrbetriq ® , FDA-approved in 2012) with a comparable limited efficacy, even if vibegron, with less side effect on blood pressure, is often preferred to mirabegron [ 5 , 6 , 7 , 8 ]. A few other options are available, including the use of botulinum toxin A, neuromodulation with implantable devices, and laser treatment but their efficacy is limited [ 9 , 10 , 11 ]. The search for novel treatment modalities and drugs continues.…”
Section: Introductionmentioning
confidence: 99%
“…UTI is another common but frustrating unfavorable outcome after intravesical BoNT-A injections [ 55 ]. A recent systemic review revealed that the prevalence rate of UTI after intravesical BoNT-A injection for treating OAB is approximately 29.8% [ 56 ]. Both storage and emptying dysfunction have been proposed to impact UTI recurrence [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common and frustrating adverse events after Botox injection for OAB are UTI and dysuria [ 33 ]. In patients with OAB, previous UTI is the strongest predictor of UTI after Botox injection.…”
Section: Clinical Application Of Botox On Oab: Efficacy Adherence Adv...mentioning
confidence: 99%
“…Current application of botulinum toxin A on lower-urinary-tract diseases or dysfunctions. ,[7][8][9][10][11][12]15,16,18,19,33,[35][36][37][38] …”
mentioning
confidence: 99%